Evaluation of Course Training Program on Research And Development Management of First Level Defense at Research and Development Agency of Defense Ministry Republic of Indonesia - Astawa, I Nyoman; Luddin, Muchlis R.; Akbar, Ma’ruf (International Journal of Scientific Research and Management (IJSRM), 2018)
The research objectives are for analyzing, assessing, and improving the course training program on research and development management of first-level defense in terms of improving research resource competencies on Ministry of Defence. The research was using the Kirkpatrick evaluation model. Datum collection techniques were constructed with observation, interview, and documentation. Validation of research has been using data reduction, present and concludes. The research results illustrated that participants who following the training was highly reacted, strong motivated, and process of science transfer well conducted. However, the alumni of the training program on research and development management of first-level defense were not optimally empowered as researchers by the organization either in research and development of the Ministry of Defense or within the TNI. Thus, the out-of-training competency of the training as a researcher has not been empowered by the organization, so the research productivity of the alumni is very low. It is recommended that the Youth ‘Litbanghan’ Training and Training program can be used as a fundamental reference in formulating the functional position of the researcher who can serve as the career path for TNI soldiers.